Do e-services and promotion affect customer loyalty? - Meitiana Meitiana; Abimanyu Tuwuh Sembhodo (Jurnal Inovasi Ekonomi, 2022)
This study aims to determine the effect of the quality of electronic services and sales promotion on customer satisfaction and loyalty, either directly or indirectly, where customer satisfaction is an intervening variable. This research is explanatory research with 96 respondents. Determination of the sample using non-probability sampling technique and applying structural equation modeling for analysis. The results of the study show that the quality of electronic services has a positive and significant effect on customer satisfaction; electronic services have no significant impact on loyalty; sales promotion has a positive and significant impact on customer satisfaction; sales promotion has a negative and significant effect on customer loyalty; customer satisfaction has a positive and significant impact on customer loyalty; the quality of electronic services has a positive and significant impact on customer loyalty through customer satisfaction. Sales promotion has a positive and significant effect on customer loyalty through customer satisfaction.